Novo registros de moscas ectoparasitas (Diptera, Streblidae e Nycteribiidae) em morcegos (Mammalia, Chiroptera) do Amazonas e Pará, Brasil1 - Graciolli, Gustavo (2002)
Species of batflies of bats from Amazonas and Pará, Brazil are reported. Eleven species of Streblidae and three of Nycteribiidae were found on nine species of bats, belonging to seven genera. Pseudostrebla greenwelli Wenzel, 1996, Trichobius affinis Wenzel, 1976, Trichobius silvicolae Wenzel, 1976, and Hershkovitzia inaequalis Theodor, 1967 were collected for the first time in Brazil. Strebla consocia Wenzel, 1966, Strebla galindoi Wenzel, 1966, Trichobius dugesioides phyllostomus Guerrero, 1998, and Trichobius joblingi Wenzel, 1966 are new records for state of Amazonas. Noctiliostrebla maai Wenzel, 1966, Basilia dubia Guimarães & D'Andretta, 1956, and Basilia ferruginea Miranda Ribeiro, 1903 are new records for state of Pará.